Zoster meningitis in an immunocompetent young patient post first dose of BNT162b2 mRNA COVID-19 vaccine, a case report. (2022) - Kerr, Colm; O'Neill, Susan; Szucs, Anna; Darmody, Oliver; Williamson, Claire; Bannan, Ciaran; Merry, Concepta
Abstract: Recently published observational data suggests an increased risk of herpes zoster infection post-vaccination with the BNT162b2 mRNA vaccine. We describe the case of VZV meningitis post BNT162b2 mRNA vaccination in a young immunocompetent patient. A 39-year-old patient with no medical history presented with a vesicular rash, headache, nausea and fever, days after receiving BNT162b2 mRNA vaccination. CSF analysis revealed a pleocytosis, and VZV DNA was confirmed by PCR testing. The patient received intravenous aciclovir with resolution of symptoms within 48 h. He was discharged after 14 days of treatment. Case reports of herpes zoster reactivation post vaccination and details of subsequent successful vaccination course completion have allowed us to recommend the patient receive his second dose of the BNT162b2 mRNA vaccine. At the time of writing, however, the patient has declined to receive further vaccination due to fears of an adverse event. To the best of our knowledge, this is the first reported case in a young patient of herpes zoster meningitis following COVID-19 mRNA vaccination. The sharing of clinical experiences and reporting of suspected side effects, particularly for vaccines that employ novel technology, increases knowledge of the safety profile of these vaccines and allows clinicians to better aid patients make informed decisions with regard to commencing and completing vaccination.